ISLAMIC POLITICS IN SUHRAWARDĪ'S THOUGHT - Setyanto, Ngarjito Ardi (Journal of Islamicate Studies, 2020)
This article discusses the concept of Suhrawardī 's thought, which was inspired by the work of Hossein Zain entitled The Source and Nature of Authority: A Study of al-Suhrawadi's Illuminationist Political Doctrine. This study is intended to try to extract Suhrawardi’s political concept of his works even though he never discusses that particular concept specifically. Through literature studies, the writer found that his political concept pivots on the definition of an ideal leader. Suhrawardī saw Prophets, kings and philosophers as ideal leaders. He believed that any philosopher can be a leader, but he/she must possess what is referred to as the spiritual aspects. He argued that a leader is not only a thinker, but spiritually he also a Sufi. On political matters, Suhrawardī clearly emphasize on the aspect of divinity. The beginning and the end of any political activity has to be on the nature of divinity.